Pengaruh Brand Image dan Promosi Terhadap Keputusan Pembelian Brand Fashion 3second (Studi Kasus Pada Mahasiswa Universitas Bhayangkara) - Manalu, Hendrick Moses Sumihar; Thamrin, Djuni (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Influence of Brand Image and Promotion on 3second Purchase Decisions (Case Study on Bhayangkara University Students). This research was conducted with the aim of finding out the brand image and promotion of the 3second purchase decision in Bhayangkara Jakarta Raya University as consumers. This research is a quantitative research where the object used is students who have bought 3second. The data used in this study is primary data. The sampling method for this number of studies uses the Lemeshow formula. The number of samples used in this study is 100 respondents. The data analysis method used to test the hypothesis in this study is Structural Equation Modeling (SEM) with the SmartPLS 4.1 application. The results of this study show that brand image and product quality on purchase decisions together (simultaneously) have a positive and significant effect on purchase decisions. This research has limitations in the object of research that is only carried out on students of Bhayangkara University Jakarta Raya, Management Study Program, Class of 2020, this can be the next researcher's suggestion. The novelty in this study is that it combines brand image and promotion variables on purchase decisions in one research model.